Estudio de factibilidad para la creación de un centro agro turístico en el sector murocomba, cantón Valencia, año 2014. - Castellano Guevara, Jessica Alexandra (2015)
The feasibility studies allow translating ideas that an individual has to make it happen, plans not only allow you to create companies in different fields, but also help to highlight the natural beauty that has a place, it is precisely what was done in this research whose theme was based on a "Feasibility study for the creation of an Agro-tourism center in Valencia Canton Murocomba sector, 2014". To carry out this project was necessary to raise four objectives, which consisted of; analyze the current situation of the tourism market of Valencia Canton, conduct a technical and economic study - financial, whereby the project's feasibility is established, meet the legal aspects based on which will accommodate the operation of Agrotourism Center and analyze the impact generating the environmental implementation. To acquire the necessary data inductive, deductive, analytical method was used, whereas the types of research were composed by applied, descriptive literature, techniques to achieve the objectives was the survey of the inhabitants of Valencia Canton. The results of the market study reflected the current situation of the tourism market in the sector is suitable for implementing the company; as this was stated by 91% of respondents who said they attend recreate some tourist center. The technical study reflected the appropriate conditions required to carry out the project, while the economic and financial study showed that it takes $ 74,409.02, investment, net income you get the Agrotourism of Murocomba Center is $ 18,988, 95, the internal rate of return is set at 17% and NPV of $ 28,561.77, and Benefit Cost Ratio of $ 2.43. As for the law to create the company are described in the second chapter of this thesis and are favorable, according to an analysis to the place it was found that the environmental impact that generate the Agroturistico Center is minimal, as it does not damage the natural look of the site, only the infrastructure will be improved and green spaces will become more attractive.